Prediction of core body temperature using infra-red thermography in buffaloes - Ashok Kumar Balhara; Mustafa Hasan Jan; Ekta Hooda; Krishan Kumar; Amandeep Ghanghas; Suman Sangwan; Sunesh Balhara; SK Phulia; Sarita Yadav; Ashok Boora; Sanjay Kumar; Sajjan Singh; et al. (Italian Journal of Animal Science)
Rectal thermometers are commonly used to assess animal health, but non-invasive methods like thermal imaging are gaining popularity for their ease. This study explores using infra-red thermography to measure eye temperatures as a proxy for body temperature in buffaloes. Among 280 adult female buffaloes, rectal temperature averaged 38.26 ± 0.38 °C, while eye temperature averaged 36.99 ± 0.47 °C. Statistical analysis showed a significant positive correlation (0.674, p < 0.001) between eye and rectal temperatures in adult buffaloes. Moderate correlations were also found between rectal temperature and ambient temperature (0.488, p < 0.001), as well as with ocular temperature (0.488, p < 0.001), while the correlation with humidity was low (0.176, p < 0.05). Regression modelling incorporating rectal and eye temperatures, ambient temperature, and humidity revealed that ocular temperature and ambient temperature significantly affect rectal temperature. The developed equation = 20.377 + 0.465(AET) + 0.024(AT) accurately predicts rectal temperature in buffaloes, with R2 of 51.6%, RMSE = 0.272, and AIC = 71.601 indicating satisfactory variability. These findings highlight the potential of thermal imaging as a diagnostic tool and provide insights into temperature measurement interrelationships.